2017
DOI: 10.1007/978-3-319-68059-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Friend: Tackling Stress Through Portable Tangible Breathing Artifact

Abstract: We present Breathing Friend-a portable and tangible device that uses haptic interaction to unobtrusively stimulate mindful breathing as efficient stress coping method. Its design is optimized for holding in user's hands. By changing its shape, it sends haptic signals to the user. Several studies were conducted where we explored and verified the form factors of the artifact, interaction methods, therapeutic effect, fitting to everyday life, and influence on the breathing pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Robots can influence the biorhythms of people; for instance, Macik et al ( 2017 ) showed that a non-humanoid robot can help entrain breathing patterns while Sato and Moriya ( 2019 ) used AI-controlled music tempo to control changes in the rate of breathing. Robots that promote sleep using rhythmic entrainment include the Somnox Sleep Robot (Mohammadi-Khanaman and Lundström, 2019 ) or the Fisher-Price “Soothe'n'Snuggle” stuffed toy ( Figure 3 ), which uses rhythmically pulsing movements, sounds and lights to help small children fall asleep.…”
Section: Part 2: Resonance In Roboticsmentioning
confidence: 99%
“…Robots can influence the biorhythms of people; for instance, Macik et al ( 2017 ) showed that a non-humanoid robot can help entrain breathing patterns while Sato and Moriya ( 2019 ) used AI-controlled music tempo to control changes in the rate of breathing. Robots that promote sleep using rhythmic entrainment include the Somnox Sleep Robot (Mohammadi-Khanaman and Lundström, 2019 ) or the Fisher-Price “Soothe'n'Snuggle” stuffed toy ( Figure 3 ), which uses rhythmically pulsing movements, sounds and lights to help small children fall asleep.…”
Section: Part 2: Resonance In Roboticsmentioning
confidence: 99%
“…To further bridge this physical gap, Macik et al in [5] propose Breathing Friend -a portable device which encourages mindful breathing as a stress coping mechanism. It uses haptic interaction to discreetly stimulate mindful breathing.…”
Section: Related Workmentioning
confidence: 99%
“…Vitali, a smart fitness bra [32] measures HRV (Heart Rate Variability) and breathing and provides cues to breathe deeply to reduce stress. Breathing Friend [21] uses haptics to stimulate breathing and Breathing Light [30] uses somaesthetics via light and sound. BrightBeat [10] uses subtle indicators in the form of sound, visual and temperature cues to influence slower breathing.…”
Section: Awareness Of Breathingmentioning
confidence: 99%